Inhibition of miR-378a-3p by Inflammation Enhances IL-33 Levels: A Novel Mechanism of Alarmin Modulation in Ulcerative Colitis - Dubois-Camacho, Karen; Diaz-Jimenez, David; De la Fuente, Marjorie; Quera, Rodrigo; Simian, Daniela; Martínez, Maripaz; Landskron, Glauben; Olivares-Morales, Mauricio; Cidlowski, John A.; Xu, Xiaojiang; Gao, Guangping; Xie, Jun; et al. (Frontiers in Immunology, 2019)
Ulcerative colitis (UC) is an inflammatory bowel disease (IBD) characterized by mucosa damage associated to an uncontrolled inflammatory response. This immunological impairment leads to altered inflammatory mediators such as IL-33, which is shown to increase in the mucosa of active UC (aUC) patients. MicroRNAs present a distorted feature in inflamed colonic mucosa and are potential IL-33 regulating candidates in UC. Therefore, we studied the microRNA and mRNA profiles in inflamed colonic samples of UC patients, evaluating the effect of a microRNA (selected by in silico analysis and its expression in UC patients), on IL-33 under inflammatory conditions. We found that inflamed mucosa (n=8) showed increased expression of 40 microRNAs and 2120 mRNAs, while 49 microRNAs and 1734 mRNAs were decreased, as determined by microarrays. In particular, IL-33 mRNA showed a 3.8-fold increase and 8 members of a microRNA family (miR-378), which targets IL-33 mRNA in the 3’UTR, were decreased (-3.9 to -3.0 times). We selected three members of the miR-378 family (miR-378a-3p, miR-422a, miR-378c) according to background information and interaction energy analysis, for further correlation analyses with IL-33 expression through RT-qPCR and ELISA respectively. We determined that aUC (n=24) showed high IL-33 levels, and decreased expression of miR-378a-3p and miR-422a compared to inactive UC (n=10) and controls (n=6). While miR-378c do not show a significant difference, miR-378a-3p and miR-422a were inversely correlated with IL-33 expression. To evaluate the possible effect of TNF-alfa on the studied microRNAs, aUC patients with anti-TNF therapy were compared to aUC receiving other treatments. The levels of miR-378a-3p and miR-378c were higher in aUC patients with anti-TNF. In base to these findings we selected miR-378a-3p to exploring the molecular mechanism involved by in vitro assays, showing that over-expression of miR-378a-3p decreased the levels of an IL-33 target sequence β-gal-reporter gene in HEK293 cells. Stable miR-378a-3p over-expression/inhibition inversely modulated IL-33 content and altered viability of HT-29 cells. Additionally, in an inflammatory context, TNF-alfa decreased miR-378a-3p levels in HT-29 cells enhancing IL-33 expression. Together, our results propose a regulatory mechanism of IL-33 expression exerted by miR-378a-3p in an inflammatory environment, contributing to the understanding of UC pathogenesis.